Produção e avaliação de briquetes ecológicos a partir de resíduos agroindustriais - CAMPOS, Keila Diniz (2021)
The objective of the research was to determine the viability of production and mechanical durability of briquettes produced by the residues of açaí kernel and cupuaçu and murumuru husks generated during the processing of these biomasses by the Cooperative of Fruit Growers of Abaetetuba/PA. Thermogravimetric analyzes and preliminary analyzes of moisture, ashes, volatile material, fixed carbon and heating power were performed on these materials after drying in a solar dryer. The briquettes were made in a constant pressure condition (15 tons) with a humidity variation between 8 to 12% w.b. of the material with a variation in the granulometric distribution (48, 60, 65 and 80 mesh) and the use of three pressing times (15, 20 and 30 minutes) for each particle size. The briquettes produced were evaluated for storage time, bulk density, energy density, impact resistance, water absorption, mechanical durability and burning of the briquettes in the boiler. The briquettes produced from açaí kernel and cupuaçu bark were of high quality in terms of mechanical characteristics, while the murumuru briquettes showed low mechanical resistance, which was expected to be a very woody biomass, but with greater heat power in relation to the other biomasses. The novelty of the research is that the briquettes were produced without the addition of any binder, with murumuru and cupuaçu as biomasses not yet tested for this social technology. After pressing and storage time of approximately 30 days, the briquettes showed good conditions of physical and mechanical properties. Only açaí stone briquettes were tested in the cooperative's boiler, proving to be very effective for replacing conventional firewood. It was concluded that the briquettes from açaí stone residue showed the best physical and mechanical properties while the briquettes from the murumuru bark residues showed the best energetic properties.